The Extraction of Nickel from Morowali Laterite Ore with Sulfuric Acid (H2SO4) - Yuliani Yuliani; Daud K. Walanda; Mery Napitupulu; Sri H. V. Pulukadang; Detris Poba (Universitas Tadulako, 2024)
Efficient recovery of valuable minerals from waste materials requires optimizing key processing parameters to maximize extraction efficiency and resource utilization. This research was conducted to determine the optimal extraction conditions, which were influenced by sulfuric acid concentration, temperature, and leaching time. This study used the Taguchi method with 3 factors and 3 levels: the concentration of sulfuric acid (H2SO4) at 0.5 M, 1 M, and 2 M; temperatures at 30 °C, 60 °C, and 95 °C; and leaching times of 3 hours, 6 hours, and 12 hours. The optimum conditions obtained from the study were a temperature of 95 °C, a leaching time of 6 hours, and an acid concentration of 2 M, with an absorbance of 0.6820. These results indicate that the Taguchi method is an efficient and reliable approach for optimizing leaching parameters, thereby contributing to the development of sustainable mineral recovery from waste materials.